Detailed carbon chemistry in charcoals from pre‐European Māori gardens of New Zealand as a tool for understanding biochar stability in soils. (8th October 2013) - Calvelo Pereira, R.; Camps Arbestain, M.; Kaal, J.; Vazquez Sueiro, M.; Sevilla, M.; Hindmarsh, J.
Summary The stability of biochar, a form of charcoal intentionally made to be added to soil to sequester carbon (C) and improve its function, remains unclear. As it is not feasible to perform long‐term (decades, centuries) laboratory experiments to assess biochar evolution after soil amendment, the study of ancient archaeological charcoals can help to identify characteristics (and possibly molecular markers) associated with the decomposition and preservation dynamics of biochar in specific pedoclimatic environments. In this study, the chemical composition of the organic carbon fractions of three charcoals from pre‐European Māori gardens of New Zealand (buried > 25 cm depth) was thoroughly assessed. Complementary short‐term incubations of charcoals in sand were used to (i) evaluate the stability of C in the short‐medium term, (ii) model its mineralization processes and (iii) estimate the C turnover. Elemental analysis, thermogravimetric analysis (TG), X‐ray photoelectron spectroscopy (XPS), solid‐state 13C nuclear magnetic resonance (NMR) and pyrolysis gas chromatography/mass spectroscopy (Py‐GC‐MS) gave consistent results in describing the charring intensity and the degree of polycondensation of these charcoals. The oldest buried deposit (770 ± 50 years BP) still retained un‐charred or weakly charred lignocellulosic material, indicating that such material survived decomposition processes for several centuries. The amount of organic C mineralized in 109 days was < 0.5% of the initial charcoal‐C. No differences in MRT among samples were detected in spite of inferred differences in thermal impact. Longer‐term incubations are needed to obtain better estimates of C turnover rates in charred material.